A rare case of community acquired meningitis caused by multidrug resistant Acinetobacter baumannii in Bengaluru India - Shil, Rahul; Das, Saikat; S., Girish Chandra M. (International Journal Of Community Medicine And Public Health, 2025)
Acinetobacter baumannii can be a potentially life-threatening cause of severe community-acquired meningitis outside healthcare facilities and as a nosocomial infection following neurosurgical procedures in intensive care units (ICUs). Despite the availability of potent newer antibiotics, mortality and complications remain high in India, ranging from 16% to 32%. Community-acquired meningitis caused by A. baumannii is relatively rare, and proper antibiotic usage and adherence to infection control protocols in hospitals should be prioritized. In this case study, we report a case of community-acquired meningitis caused by A. baumannii in Bangalore without any prior history of neurosurgical complications or trauma.